Fresno County Bar Association Annual Bar Banquet at TorNino's - Watkins, Howard::::::::: (1985)
Joe Uremovic seated; standing: Robert Sears, ?, William Seiler, Richard Watters, Donald Franson, Jr. and Carmen Eanni